Effect of Procedural Justice, Perceived Safety and Forgiveness in Nigeria’s Domestic Airline Service - Sany Sanuri Mohd Mokhtar; Haliru Muhammad (International Journal of Supply Chain Management, 2017)
Exertions were made by service firms to address issues of service failure. Particularly, through effective strategy that enhance customer satisfaction and subsequent retention of customer. This study conceptualizes and empirically validates a model exploring the relationship between procedural justice, perceived safety, forgiveness constructs and satisfaction service recovery of domestic airline passengers of Nigeria. Sample of 444 domestic airline passengers by the use of cluster sampling technique were obtained for the study. The data were analyzed by the use of PLS technique. Results obtained recommend that the perceived safety procedural justice, and forgiveness have a significant effect on satisfaction service recovery. Theoretical and practical implications of the study were as well discussed and conclusions drawn.